Perception of Soviet Kazakhstan in emigrant publicism: an analysis of the works of Hasan Oraltay - Aktailak, B.B.; Ibraemova, M.S.; Nabiyev, S.T. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
This article is an analysis of the discourse of Soviet Kazakhstan in emigrant journalism. The main source is the works of Hasan Oraltay, a prominent Kazakh scientist and public figure. H. Oraltay had a deep knowledge of political and social processes in Kazakhstan and conducted systematic research into the issues of ethnicity and power in the republic throughout the 20th century. The proposed study, based on the works of Hasan Oraltay, examines the pivotal events and developments that shaped the history of Kazakhstan in the 20th century. The study focuses on the formation of the Kazakh national identity, the development and evolution of the autonomist movement, the rise of the Bolsheviks and the subsequent consolidation of Soviet power in the republic. Particular attention is paid to the role of the Kazakh intelligentsia, the Alash Party and the Alash-Orda government in the context of these historical events. The study enables an analysis of the stance adopted by Kazakh political elites towards Soviet power and an evaluation of the influence exerted by these processes on the subsequent evolution of Kazakh society.
Кеңестік Қазақстанды эмигранттар публицистикасында қабылдауы: Хасан Оралтай шығармашылығын талдау
Восприятие советского Казахстана в эмигрантской публицистике: анализ трудов Хасана Оралтая
Keywords: Kazakhs abroad; Kazakh intelligentsia; Alash; Hasan Oraltay; Soviet Kazakhstan; Soviet power; emigration; national identity